The role of haptics in immersive telecommunication environments - Reiner, M. (IEEE transactions on circuits and systems for video technology, 2004)
This paper explores the role of haptics in immersive telecommunication applications and analyzes the contribution of haptics to the sense of presence in a variety of applications. Based on the concept of embodied presence, a new construct, resonance between the human cognitive-body system and the streaming sensory information from the environment, is suggested to be a principal factor in "presence." Resonance is defined as the level of mutual synergy between sensory information and action, relative to the physical environment. It occurs when the sensory flow supports action. Since the human haptic system is unique in that it both perceives sensations from the environment and acts on the environment, it has a central role in resonance and in presence. Haptics in the natural world supports efficient bodily action and, in a tacit way, supports development of higher reasoning skills. This requires resonance and embodied presence. The current visual-haptic gap between levels of technological development creates a bottleneck in developing fully tele-immersive applications.